If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + 10 = -18 + -5X Reorder the terms: 10 + 2X = -18 + -5X Solving 10 + 2X = -18 + -5X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '5X' to each side of the equation. 10 + 2X + 5X = -18 + -5X + 5X Combine like terms: 2X + 5X = 7X 10 + 7X = -18 + -5X + 5X Combine like terms: -5X + 5X = 0 10 + 7X = -18 + 0 10 + 7X = -18 Add '-10' to each side of the equation. 10 + -10 + 7X = -18 + -10 Combine like terms: 10 + -10 = 0 0 + 7X = -18 + -10 7X = -18 + -10 Combine like terms: -18 + -10 = -28 7X = -28 Divide each side by '7'. X = -4 Simplifying X = -4
| x+6*3=22 | | -16=x+71 | | 1/5y-5=-15 | | X*3=10 | | t^2-23t=0 | | x/27=-2/9 | | 1/8x=-12 | | 3+7n=-2(3n+8)+6 | | 9x-1=5x+7 | | z^2+(1+i)z-2+2i=0 | | 45=-5(m-6) | | 10y-8+10y=8 | | -2.5x+1.8-1.6x=5.7 | | -3(p-6)=36 | | 3x^7-24x^6+12x^5=0 | | 4y(6y^2+7y+6)= | | -2(z+3)-z=-z-4(z+z) | | 4=(2m+3)(3-m) | | 3+4(8x-8)=-61 | | 7+6-4+3= | | (2b-3.4)/0.6=-29 | | (2b-3.4)/8=5 | | 79+x=8(x+2) | | x^2+4x+7=4 | | 10+(6)(5)= | | -3k-4=1-k+3k | | 2(x+4)=10+5 | | -0.75-2=0.25 | | 1/4(x-10)=6 | | .27=logx | | -3+2x=2x+x-6 | | 4+1*5-2+1= |